Feminism and the Indonesian nationalist movement: A reading of Soewarsih Djojopoespito’s novel Buiten het Gareel - C. W. Watson, (Universiti Kebangsaan Malaysia, 2009)
Soewarsih’s autobiographical novel written in Dutch describes the difficulties facing Dutch educated Indonesians involved in the anti-Dutch nationalist movement in the late 1930s. It deals specifically with the role which women played within the movement and how their male counterparts took an ambivalent attitude towards them. In terms of its subject matter and its construction the novel reflects the sense of crisis of the first generation of Indonesians to have been exposed to Dutch/European culture with which they identified but which at the same time they felt they had to repudiate. Relying on a close reading of the text and references to critical works dealing with the author and the period, this article demonstrates how Soewarsih deliberately uses the novel both to give voice to her personal frustrations as a woman and to offer personal testimony of the atmosphere and events of the times. It also argues through this example that in all our postcolonial reading we must be cautious when we make use of autobiographical sources and contemporary novels to reconstruct perceptions of the past, and we need to ensure that, when reading the texts, we employ literary, anthropological and historical critical skills in equal measure